Parental Comprehension of Standard and Simplified Information Consent Forms in a Pediatric Clinical Trial Simulation – A Randomized Controlled Study - Lord, Claudia; Gauthier, Gabrielle; Legault, Emma; Mitrea, Irina; Gogognon, Patrick; Roy, Hélène; Lebel, Denis; Bédard, Pascal; Métras, Marie-Élaine (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
Background: Informed consent forms (ICFs) are a mandatory prerequisite for participating in clinical trials. In pediatric studies, the ICF is generally signed by the child’s parents. The ICFs designed for clinical trials are often lengthy and complex to understand. We conducted this study to determine if a simplified ICF would improve parental understanding compared to a standard ICF. Methods: A single-centre, single-blind, randomized controlled trial featuring two fictitious ICFs took place in a tertiary Canadian mother and child university hospital. Parents of hospitalized children were assigned to read either a standard or simplified ICF. Parental comprehension was measured using the Modular Informed Consent Comprehension Assessment (MICCA) questionnaire. The primary outcome of this study was to assess the proportion of parents with a MICCA score of 75% or above. Results: One hundred and fifty participants answered the study questionnaires. The primary endpoint was reached by 55.7% of the participants who read the simplified ICF compared to 46.2% in the standard ICF group (p=0.303). The mean MICCA scores were 17.87 and 17.75 points, respectively (p=0.847). Themes that were poorly understood by both groups were the study procedures, the adverse effects, the other available treatment options as well as the main benefits and purpose of the study. Conclusion: This single centre, single-blind, randomized controlled study showed that the comprehension was similar between a simplified and a standard ICF. This suggests that using simplified ICFs does not improve nor impair parental comprehension. Therefore, a simplified ICF should be used as frequently as possible in pediatric research projects.